2003
DOI: 10.1046/j.1365-313x.2003.016011.x
|View full text |Cite
|
Sign up to set email alerts
|

The chlorate‐resistant and photomorphogenesis‐defective mutant cr88 encodes a chloroplast‐targeted HSP90

Abstract: SummaryThe cr88 mutant of Arabidopsis is a novel chlorate-resistant mutant that displays long hypocotyls in red light, but not in far red or blue light, and is delayed in the greening process. In cotyledons and young leaves, plastids are less developed compared with those of the wild type. In addition, a subset of light-regulated genes are under-expressed in this mutant. To understand the pleiotropic phenotypes of cr88, we isolated the CR88 gene through map-based cloning. We found that CR88 encodes a chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 94 publications
5
88
0
2
Order By: Relevance
“…S2). Although Hsp90C is present in chloroplasts from all plant species examined (18,19), its role in chloroplast function and biogenesis has not been examined in detail. Our data suggested that Hsp90C is involved in the import or suborganellar targeting of atTic40.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S2). Although Hsp90C is present in chloroplasts from all plant species examined (18,19), its role in chloroplast function and biogenesis has not been examined in detail. Our data suggested that Hsp90C is involved in the import or suborganellar targeting of atTic40.…”
Section: Resultsmentioning
confidence: 99%
“…Specific subfamilies of the Hsp90s exist in prokaryotes and multiple organelles in eukaryotes, including the cytosol, the ER (glucoseregulated protein 94, Grp94) (33), mitochondria (TNF receptorassociated protein 1, TRAP1) (34), and chloroplasts (Hsp90C) (18). Cytosolic Hsp90 has been studied extensively, and its participation, with a number of cochaperones, in the targeting, assembly, and stability of multiprotein complexes has revealed critical roles in protein folding, cellular signaling, and protein trafficking (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations